Polyspecificity - An emerging trend in the development of clinical antibodies. (March 2023) - Sandeep,; Shinde, Suraj H.; Pande, Abhay H.
Abstract: The essence of the growth and development of therapeutic conventional monoclonal antibodies (MAbs) for the treatment of various disorders is the aptitude of MAbs to precisely bind a target antigen and neutralise or promote its activity. However, the conventional antibodies are monoclonal i.e., both paratopes bind to the same epitope. But most of the pathophysiological conditions are multifaceted, hence targeting/blocking/inhibition of more than one epitope/antigen is more promising than one epitope/antigen. Polyspecific antibodies (PsAbs) have the potential to concurrently bind to more than one target and are the next-generation antibodies that augment efficacy in both clinical and non-clinical contexts. Thus, the trend of engineering and developing various formats of PsAbs is emerging. In this review, we have briefly discussed the importance of antibody polyspecificity and PsAbs approved for clinical use. Subsequently, we have discussed the role of TNF-α and IL-23 in inflammatory diseases and stressed the need for developing anti-TNF-α and anti-IL-23 bispecific antibodies. Highlights: Monoclonal antibodies targeting single epitope/antigen having number of promising clinical and non-clinical applications. Now the trend is changing to polyspecific antibodies targeting more than one epitope/antigen simultaneously. Chronic inflammation claims 3 deaths out of 5 individuals worldwide. TNF-α and IL-23 both are main drivers of chronic inflammation, inhibiting their interactions with their respective receptors using polyspecific antibodies is one of the intriguing treatments to control chronic inflammation. One promising approach to reducing inflammation is the use of PsAb to block TNFα and IL-23 from binding to their receptors.